GENERAL GEOLOGY OF KAMPUNG GUNUNG SEMANGGOL, BUKIT MERAH WITH EMPHASIS ON REGIONAL STRUCTURAL AND SEDIMENTARY STYLES AND FABRIC - Bin Mohd Aminuddin, Mohd Rashid (Universiti Teknologi PETRONAS, 2015)
Kampung Gunung Semanggol is located in the region of the Semanggol Formation in the Malay Peninsula. The project’s objective is to study the geology of the area with emphasis on the regional sedimentary structural styles and fabric. The study will be focusing on the Semanggol Formation and its members which made up by the three main lithological members which are the chert member as the oldest, followed by the ryhtmite member which is the interbedded shale and sand and the youngest member of conglomerate. The focus will be more onto observing the sedimentary patterns and their fabric while identifying the lithology of the area. All of the observation data by logging, measuring strike and dip and the laboratory test will be compiled and analysed to produce some deliverables. The deliverables include the base map, lithological map and the cross section map which are the main products of this project. The area is basically made up of sandstone with some thick bed of shale found in the outcrop. From the structural observation, the orientation is mostly in N-S orientation but there is disorientation (in almost W-E direction) occur in the area which most probably be related with the local stress regime. From the stratigraphical analysis, the previous depositional environment is most probably in the middle fan channel of submarine fan. The fabric and mineral composition shows the sandstone is sublitheranite and is in immature stage.